Pemetaan Deformasi Gunung Api Menggunakan Metode Diffrential Interferometry Syntetic Aperature Radar (DInSAR): (Studi Kasus: Gunung Marapi, Sumatera Barat) - Ulfah Umniyyah; Dwi Arini; Fajrin; Dwi Marsiska Driptufany (Jurnal Sains dan Ilmu Terapan, 2026)
Mount Marapi is one of the most active volcanoes in West Sumatra with frequent eruptions and significant volcanic activity in recent years. Monitoring surface deformation is essential to understand subsurface magma dynamics and support volcanic hazard mitigation. This study aims to analyze surface deformation of Mount Marapi using the Differential Interferometric Synthetic Aperture Radar (DInSAR) method based on Sentinel-1 satellite imagery. The data used in this study cover the period from January 2023 to March 2025. Processing was carried out using SNAP software to generate interferograms and deformation maps. The results indicate spatial variations of deformation in the form of uplift and subsidence around the volcanic edifice. Uplift is interpreted as magma pressure or fluid movement beneath the surface, while subsidence may indicate deflation or material compaction after eruptions. These findings demonstrate that DInSAR is effective for monitoring volcanic deformation and can support early warning systems for volcanic hazards.